The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
40th AIAA Aerospace Sciences Meeting &Amp; Exhibit 2002
DOI: 10.2514/6.2002-336
|View full text |Cite
|
Sign up to set email alerts
|

Reduced chemical kinetic mechanisms for JP-8 combustion

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. ABSTRACTUsing CARM (Computer Aided Reduction Method), a computer program that automates the mechanism reduction process, six different reduced chemical kinetic mechanisms for JP-8 combustion have been generated. The reduced mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 9 publications
(11 reference statements)
0
32
0
Order By: Relevance
“…The choice of constituents in a surrogate mixture is dependent on the aspects of the combustion processes that are targeted for modeling. For practical combustion devices these intended targets include performance criteria such as combustion efficiency, ignition delays, and pollutant formation [2]. Iso-octane and n-heptane are the primary reference fuels for octane rating and are widely used constituents of gasoline surrogates.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of constituents in a surrogate mixture is dependent on the aspects of the combustion processes that are targeted for modeling. For practical combustion devices these intended targets include performance criteria such as combustion efficiency, ignition delays, and pollutant formation [2]. Iso-octane and n-heptane are the primary reference fuels for octane rating and are widely used constituents of gasoline surrogates.…”
Section: Introductionmentioning
confidence: 99%
“…To supplement the compressed air cooling of the nozzle, copper coils were wrapped around the nozzle to feed chilled water to it. The chemical byproducts of the propane combustion in the HVOF were similar to those of the gas turbine engines, such as JP-8 [25][26][27][28][29]31]. Flow rates of reactants (i.e., propane and oxygen) and cooling air could be adjusted and calibrated to produce the open flame of required combustion environments.…”
Section: Combustion-load Test Setupmentioning
confidence: 99%
“…Investigation of an oxide/oxide (Nextel 720/alumina) CMC under the combination of mechanical loads and combustion environment showed that fatigue strength and ultimate tensile strength had a small degradation (about 20 %) under the combustion environment in comparison to its counterpart under the ambient laboratory environment [28,29]. The effects of different parameters on mechanical performance of CMCs including combustion fatigue are discussed in [30][31][32]. CMCs exposed to burner rig cycles without any load showed a small degradation in strength (*15 %) relative to that from the as-fabricated state [33].…”
Section: Introductionmentioning
confidence: 98%
“…Violi signed to match the volatility of jet fuel and its overall sooting behavior based on smoke point tests. More recently, the number of components has further decreased [7][8][9], with the minimization effort culminating in the two-component Aachen surrogate [10]. Single-component surrogates, though initially contemplated, are now generally thought to lack the necessary flexibility to match the jet fuel performance in a sufficiently broad parameter space.…”
Section: Introductionmentioning
confidence: 98%